2019
DOI: 10.1002/ajcp.12358
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Engaged Neighborhood Revitalization and Empowerment: Busy Streets Theory in Action

Abstract: Busy streets theory predicts that engaging residents in physical revitalization of neighborhoods will facilitate community empowerment through the development of sense of community, social cohesion, collective efficacy, social capital, and behavioral action. Establishing safe environments fosters positive street activity, which reinforces neighborhood social relationships. A community‐engaged approach to crime prevention through environmental design (CE‐CPTED) is one promising approach to creating busy streets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…It can be concluded that the theoretical and empirical analysis of the environmental characteristics of criminal acts has achieved fruitful results in the world. The research perspective runs through social and physical factors, and the content of social factors such as population structure which influence the distribution of potential criminals and victims (Kauzlarich and Barlow 2009;Shaw and McKay 1972;Rupp et al 2019), flow density (Rupp et al 2019), policing distance (변성수 and 배민기 2019) and so on; physical environmental factors include environmental visibility (Fujii, Fujikawa, and Oikawa 2013), space permeability (Cozens 2008), access control ability (Weisel 2004) and environmental aesthetics (Roh and Park 2017), which provide an effective basis for the prediction of urban internal crime in this paper.…”
Section: Overview Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the theoretical and empirical analysis of the environmental characteristics of criminal acts has achieved fruitful results in the world. The research perspective runs through social and physical factors, and the content of social factors such as population structure which influence the distribution of potential criminals and victims (Kauzlarich and Barlow 2009;Shaw and McKay 1972;Rupp et al 2019), flow density (Rupp et al 2019), policing distance (변성수 and 배민기 2019) and so on; physical environmental factors include environmental visibility (Fujii, Fujikawa, and Oikawa 2013), space permeability (Cozens 2008), access control ability (Weisel 2004) and environmental aesthetics (Roh and Park 2017), which provide an effective basis for the prediction of urban internal crime in this paper.…”
Section: Overview Of Studymentioning
confidence: 99%
“…Social indicators include population structure (distribution of potential criminals and victims) (Kauzlarich and Barlow 2009;Shaw and McKay 1972;Rupp et al 2019), community flow density (Rupp et al 2019), police deterrent strength (변성수 and 배민기 2019), and other factors. Indicators that can be used for data processing are selected as follows:…”
Section: Experimental Designmentioning
confidence: 99%
“…Rappaport (1987) defined empowerment as the interdependent process at the individual (psychological), organizational, and community levels, which focuses on how individuals (and groups) obtain and utilize resources to assert control and change their environmental circumstances. Due to the utility of empowerment, it has been defined and applied across numerous disciplines that include community psychology (Lardier Jr, Reid, & Garcia‐Reid, 2018; Peterson & Reid, 2003; Rappaport, Rappaport, Swift, & Hess, 1984; Zimmerman, 1995, 2000), social work (Itzhaky, Zanbar, Levy, & Schwartz, 2015; Powell & Peterson, 2014), community organizing (Christens, Peterson, & Speer, 2014; Rupp et al., 2020; Zanbar, 2019); and health care promotion research (Cicognani, Albanesi, Valletta, & Prati, 2019; Cyril, Smith, & Renzaho, 2015; Wallerstein, 2002; Wallerstein & Bernstein, 1988). Empowerment theory considers the assets and abilities that are fostered within individuals and communities to improve lives.…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment theory considers the assets and abilities that are fostered within individuals and communities to improve lives. It has been broadly applied to studies examining individual wellbeing (Christens et al., 2014; Itzhaky et al., 2015; Lardier Jr, 2019; Opara, Lardier Jr, Fernandez, Garcia‐Reid, & Reid, 2020; Peterson, Speer, & Peterson, 2011), aspects of healthy communities (Rupp et al., 2020), and interventions that foster empowerment among participants (Peterson et al., 2011; Zimmerman, 1995, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Further, while growing attention has been devoted to understanding the nature of empowering settings, few studies have examined how such settings can influence the broader community and facilitate social change. For example, some studies have examined community empowerment and health‐related outcomes (See Laverack, 2006 for a review), while others have examined neighborhood safety related outcomes (e.g., Rupp et al, 2019). This growing body of literature demonstrates the importance of collective ownership of programs (e.g., Kerrigan et al, 2015), community‐driven programming (e.g., Kerrigan et al, 2015), community cohesion (e.g., Kerrigan et al, 2015; Rupp et al, 2019), and social capital (Rupp et al, 2019).…”
Section: Introductionmentioning
confidence: 99%